Potomac River as sailed by watermen of the Optimist Club, Bushwood, MD - Frederick Tilp (1970)
Hand-drawn color map of the Potomac River and adjoining locations in VA & MD. Sketches of six sailing vessels along with their captain's name. Historical events are noted.